Reticulate Evolution, Ancient Chloroplast Haplotypes, and Rapid Radiation of the Australian Plant Genus Adenanthos (Proteaceae) - Nge, Francis J.; Biffin, Ed; Thiele, Kevin R.; Waycott, Michelle (Frontiers in Ecology and Evolution, 2021)
Cytonuclear discordance, commonly detected in phylogenetic studies, is often attributed to hybridisation and/or incomplete lineage sorting (ILS). New sequencing technologies and analytical approaches can provide new insights into the relative importance of these processes. Hybridisation has previously been reported in the Australian endemic plant genus Adenanthos (Proteaceae). Like many Australian genera, Adenanthos is of relatively ancient origin, and provides an opportunity to examine long-term evolutionary consequences of gene flow between lineages. Using a hybrid capture approach, we assembled densely sampled low-copy nuclear and plastid DNA sequences for Adenanthos, inferred its evolutionary history, and used a Bayesian posterior predictive approach and coalescent simulations to assess relative contributions of hybridisation and ILS to cytonuclear discordance. Our analyses indicate that strong incongruence detected between our plastid and nuclear phylogenies is not only the result of ILS, but also result from extensive ancient introgression as well as recent chloroplast capture and introgression between extant Adenanthos species. The deep reticulation was also detected from long-persisting chloroplast haplotypes shared between evolutionarily distant species. These haplotypes may have persisted for over 12 Ma in localised populations across southwest Western Australia, indicating that the region is not only an important area for old endemic lineages and accumulation of species, but is also characterized by persistence of high genetic diversity. Deep introgression in Adenanthos coincided with the rapid radiation of the genus during the Miocene, a time when many Australian temperate plant groups radiated in response to large-scale climatic change. This study suggests that ancient introgression may play an important role in the evolution of the Australian flora more broadly.